A comparative study of fissure sealants Helioseal Clear Chroma and Delton FS(+): 3 year results. - (:unkn) unknown (My University, 2009)
AIM: To evaluate the retention rates of a resin based colour changing fissure sealant (Helioseal Clear Chroma; Ivoclar Vivadent AG Schaan, Liechtenstein) compared with a coloured resin based fluoride fissure sealant (Delton FS(+); Dentsply De Trey GmbH,Konstanz,Germany). METHODS: The fissure sealants (FS) were placed on all 4 caries-free first permanent molars of 31 children aged 6-9 years, using a half mouth experimental design by a paediatric dentist according to the manufacturers' instructions. A total of 121 FS were placed at baseline. Teeth were evaluated at 3 month intervals for 36 months where a preventive program including topical fluoride application was applied. RESULTS: Retention rates for 36 months showed a differences between Delton FS(+) and Helioseal Clear Chroma that were statistically significant (p<0.05). Delton FS(+) had total retention rate of 30.4% for 36 months compared with Helioseal Clear Chroma at 10.8% for the same evaluation period. Although Delton FS(+) showed significantly better results than Helioseal Clear Chroma for the evaluation periods, there were no statistically significant differences between Delton FS(+) (90.7%) and Helioseal Clear Chroma (80.4%) with respect to caries incidence at 36 months(p>0.05). CONCLUSION: Delton FS(+) showed a better complete retention rate for occlusal FS at one year. Both FS were aesthetically acceptable and easy to see during application and follow-up periods and gave significant protection from occlusal decay.